Analysis of the economic competitiveness of the potential of electric energy production from biogas from bovine waste in Alagoas / Análise da competitividade econômica do potencial de produção de energia elétrica a partir do biogás proveniente de dejetos bovinos em Alagoas - Eliel Santana Filho; Jerusa Maria Oliveira; Jerusa Góes Aragão Santana; Andrea Vasconcelos Freitas Pinto (); Sarah Jacqueline Cavalcanti da Silva; Elton Lima Santos (Universidade Estadual de Alagoas, 2018)
Brazil has a large hydroelectric source, but it faces energy supply challenges caused by variations in the rainfall regime and growing demands for the maintenance of biomes. This reality has driven the search for other renewable alternatives. This work analyzed the economic possibilities for the use of bovine wastes from the Alagoas herds for electric power generation in properties at different scale values. This allows them to be economically strengthened either by reducing the costs paid to concessionaires or by the possibility of industrialization activities with a decentralized and safe energy supply. From the identification of the sizes of herds in the state, we propose generation scales and analyze the rates of returns and payback returns for these plants. The results show that the discounted reimbursements for the installed power of 75kW, which require a stock of 500 animals, is above 16 years which shows little attractiveness for this scale. This same indicator is reduced to a little more than 6 years for the upper limit of installed capacity of 1000kW. Since this high capacity demands a source of more than 13,000 animals, it can be applied in a very restricted number of property in the state, characterized by small farms. The output goes through developments to reduce investment costs, producer associations and government support.